Pendidikan Wawasan Kebangsaan Di Era Globalisasi - Siregar, Nurmayana (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this study is to describe how the implementation of national insight education in the era of globalization. This study uses a qualitative approach, which describes and describes the implementation of national insight education in the era of globalization. The data collection technique used in this research is library research, where library research is the activity of collecting materials related to research from scientific journals, literatures, and authors. The data analysis technique used in this research is qualitative data analysis, which in this study is in the form of opinions expressed by experts regarding national insight education. This study has the result that the implementation of national insight education in the era of globalization is through civic education.